Finite element analysis of the effect of framework materials at the bone-implant interface in the all-on-four implant system - Kasturi Chandrashekhar Kelkar; Vinaya Bhat; Chethan Hegde (Wolters Kluwer Medknow Publications, 2021)
Background: The "All-on-four" concept for treatment of edentulous arches incorporates four implants that are placed in between mental foramina in the mandible. The prosthetic framework is an important parameter in stress/strain concentration at the implants, prosthesis, and the underlying bone. Materials such as titanium, zirconia, and carbon fibers have been used for fabrication of framework in the past. The aim of this study was to analyze the effect of framework materials in the "All-on-four" implant system. Materials and Methods: Finite element three-dimensional (3D) model of edentulous mandible was simulated using a computerized tomographic scan data of an edentulous patient. Threaded implants were replicated along with the abutments using 3D modeling software and the framework was designed and simulated using material properties of titanium, zirconia, and polyetheretherketone (PEEK). Axial and nonaxial load of 200 N was applied at the abutment region of right distal implants. The computer-generated numerical values were tabulated and analysed by ANSYS software. Results: Principal strain, von Mises stress and micromotion were assessed in the peri-implant bone region to evaluate its stress condition. Zirconia framework showed the least stress/strain values at axial and oblique loading. Maximum strain values were seen at the PEEK framework material. Zirconia framework in all models showed the least micromotion/displacement. Conclusion: The stress distribution pattern at implant-bone interface was influenced by the framework material used. The framework material, loading site, and direction of forces influenced the stresses and displacement at the bone-implant interface.